1990
DOI: 10.1159/000186106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pulmonary Accumulation of Labelled Neutrophils by Blood Membrane Contact in the Pig

Abstract: Nine anesthetized pigs were subjected to short (90 min) sham dialysis with blood membrane contact with the aim to select effects of the artificial surface during dialysis. The importance of the neutrophil (PMN) was investigated by the selective isotope labelling, dynamically followed by γ-camera imaging and biochemical assays specifically oriented for PMN function. These assays included cell count, PMN aggregation, PMN luminescence, fibronectin and catalase activity. Aditionally, pulmonary and systemic hemodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We have previously shown that PMNs aggregate in the lungs quickly after the start of dialysis, reaching a maximum after 10-15 min and simultaneously a drop in the PMN count in peripheral blood occurs [3]. A rise in PAP was noted prior to the increase in PMN sequestration.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We have previously shown that PMNs aggregate in the lungs quickly after the start of dialysis, reaching a maximum after 10-15 min and simultaneously a drop in the PMN count in peripheral blood occurs [3]. A rise in PAP was noted prior to the increase in PMN sequestration.…”
Section: Discussionmentioning
confidence: 83%
“…Mean systemic blood pressure (MAP) and heart rate were monitored continuously via a catheter in the left carotid artery. Blood samples for peripheral cell count including white blood cells, red blood cells and platelets were obtained from dialysis tubings and analyzed as previously described [3], Arterial and pulmonary blood samples for determination of blood gases and saturation were ob tained from the neck catheters and analyzed by standardized labora tory techniques. After a period of stabilization and baseline determina tion a sham dialysis using cuprophan hollow-liber dialysers (0.80 m2) was commenced and continued for 60 min as previously described [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that neutrophils become sequestered in the lungs early after trauma and the beginning of dialysis [5,10]. Although clinical signs of respiratory insufficiency during the early phase of sepsis are usually not seen, it could be hypothezised that the activation and pulmonary sequestration of PMNs occurs at this early stage [7].…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal circulation also seems to influence the blood cells, causing aggregation and accumulation of platelets and neutrophiles Correspondence : Dr John Jahr, Department of Physiology and Neuroscience, University of Lund, So$ lvegatan 19, S-223 62 Lund, Sweden. (Colman 1990, Ma/ rtensson et al 1990, as well as interfering with the normal coagulation system (Webb et al 1995, Edmunds 1993) and generating complement activation (Blomquist et al 1991, Kirschfink et al 1993. Some of these questions were addressed by us in a previous experimental study (Jahr & Gra$ nde 1992), in which we showed that long-term extracorporeal veno-venous circulation including a roller-pump had severe adverse effects in terms of respiratory insufficiency, platelet consumption, transcapillary leakage and acidemia and that these adverse effects were partly counteracted by prostacyclin.…”
mentioning
confidence: 99%